Revitalisasi Pendidikan Kewarganegaraan sebagai Sarana Penguatan Karakter Bangsa - Zakaria Bintang Pamungkas; Urwatul Wutsqah (Hikamatzu | Journal of Multidisciplinary, 2025)
This study aims to examine the strategic role of Civic Education in strengthening national character and to explore revitalization strategies to make it more effective in the current era. Through a literature review approach, the research analyzes the challenges and opportunities in integrating character education into Civic Education, especially in the context of globalization and moral degradation among the younger generation. The findings indicate that Civic Education, when implemented through an updated curriculum, contextual learning methods, and active teacher involvement, can significantly contribute to the internalization of national values such as honesty, responsibility, tolerance, and patriotism. Furthermore, the success of character building through Civic Education also requires strong collaboration between schools, families, and communities. Thus, revitalizing Civic Education is essential not only to impart civic knowledge but also to shape responsible and value-oriented citizens who uphold the moral foundations of the Indonesian nation.